2004
DOI: 10.1111/j.1396-0296.2004.04020.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical peeling in ethnic/dark skin

Abstract: Chemical peeling for skin of color arose in ancient Egypt, Mesopotamia, and other ancient cultures in and around Africa. Our current fund of medical knowledge regarding chemical peeling is a result of centuries of experience and research. The list of agents for chemical peeling is extensive. In ethnic skin, our efforts are focused on superficial and medium-depth peeling agents and techniques. Indications for chemical peeling in darker skin include acne vulgaris, postinflammatory hyperpigmentation, melasma, sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 32 publications
1
90
0
1
Order By: Relevance
“…28 As a peel it is self-neutralizing, typically creating a white frost on the skin, which is not desired in SPT IV-VI due to the risk of dyschromias and scarring. 8 Chun et al 29 evaluated the use of varying concentrations of TCA (10-65%) pressed firmly and focally onto a range of benign pigmentary disorders (65% TCA for seborrhoeic keratosis, 50-65% TCA for solar lentigines and freckles and 10-50% TCA for melasma) in 106 patients with SPT IV and V. No significant complications were observed, and patient satisfaction rates ranged from 55% for melasma to 86% for seborrhoeic keratosis.…”
Section: Trichloroacetic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…28 As a peel it is self-neutralizing, typically creating a white frost on the skin, which is not desired in SPT IV-VI due to the risk of dyschromias and scarring. 8 Chun et al 29 evaluated the use of varying concentrations of TCA (10-65%) pressed firmly and focally onto a range of benign pigmentary disorders (65% TCA for seborrhoeic keratosis, 50-65% TCA for solar lentigines and freckles and 10-50% TCA for melasma) in 106 patients with SPT IV and V. No significant complications were observed, and patient satisfaction rates ranged from 55% for melasma to 86% for seborrhoeic keratosis.…”
Section: Trichloroacetic Acidmentioning
confidence: 99%
“…Photoprotection and bland emollients should be started immediately after the peel, and wetting the area should be avoided for 24 h, followed by a return to normal cleansing activities. 8 One week after the peel, hydroquinone and topical retinoid therapy may be restarted.…”
Section: Pre and Post-peel Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Salycilic acid is also commonly used in dermatology in anti-acne treatments. 28,29 Abudance of salycilic acid in R. intermedia bark indicated that salycilic acid is probably the active component in bark of some Rhamnus species used in Bosnia and Herzegovina to treat mange and skin diseases.…”
Section: Phytochemicals Contentmentioning
confidence: 99%
“…Africans and darker African Americans (skin types V and VI) have better results with salicylic acid peels because the risk for PIH is higher with glycolic acid peels. Finally, serial glycolic acid peels and salicylic acid peels have been successful in improving the skin texture in patients with pseudofolliculitis barbae [22].…”
Section: Ethnic Skin Considerationsmentioning
confidence: 99%